Role of antimicrobial photodynamic therapy for the management of peri‑implant diseases among habitual nicotinic product users: A systematic review - Abdulrahman M. AlMubarak (Photodiagnosis and Photodynamic Therapy)
Objective: The objective was to systematically review original studies that assessed the influence of antimicrobial photodynamic therapy (aPDT) for managing peri‑implant diseases among habitual nicotinic product (NP) users. Methods: The research question was “Is aPDT effective for managing peri‑implant diseases among NP users?” Indexed databases (PubMed/Medline, EMBASE, Scopus, and ISI Web of Knowledge) and Google Scholar were searched up to and including December 2024 without time and language barriers. Using Boolean operators, the following keywords were searched in different combinations: antimicrobial photodynamic therapy; crestal bone loss; peri‑implant diseases; probing depth; nicotine; and smoking. Original clinical studies were included. Letters to the Editor, Case-reports, case-series, commentaries, reviews and perspectives/expert opinions were excluded. The literature search was performed in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-analyses. The risk of bias (RoB) was assessed using the Cochrane RoB 2 tool. Results: Seven RCTs performed on adult males were included and processed for data extraction. The mean ages of participants ranged between 31 and 57 years. The wavelength of the diode laser ranged between 660 and 670 nm in all studies. Results from all RCTs showed that aPDT, when performed as an adjunct to MD, is more effective in reducing peri‑implant plaque index, bleeding scores, and peri‑implant PD in contrast to when mechanical debridement (MD) was performed alone. None of the studies reported a statistically significant difference in crestal bone height, irrespective of whether MD was done with or without adjunct aPDT. In all studies, the follow-up duration ranged between 3 and 12 months. The aPDT was performed once (after MD) in all studies. All studies had a low RoB and their results were based on power-adjusted data. Conclusion: In the short term, a single session of aPDT as an adjunct to MD effectively reduces peri‑implant soft-tissue inflammation among NP users with peri‑implant diseases. However, this treatment does not influence CBL in these patients.